Contributing to a World Free from Hunger, Malnutrition, Poverty and Inequality: Framework for Gender-Responsive Livestock Development launches at the Climate and Clean Air Conference - Spinelli, Madison (CGIAR System Organization, 2024)
A blog post on the launch of 'A Framework for Gender-Responsive Livestock Development' launch at the Climate and Clean Air Conference 2024 in Nairobi, Kenya.